Media and War: Social Media Used by Russia and Ukraine as a Propaganda Tool During the Invasion - Makatita, Gamal Abdul Nasir; Hussin, Mutia Hariati (The Indonesian Islamic Studies and International Relations Association (Insiera), 2024)
This paper examines how media was used as a propaganda tool during Russia's invasion of Ukraine, analyzing the strategies employed by both Russia and Ukraine to disseminate propaganda, shape public opinion, and influence international perceptions. Understanding the intricate relationships between media, misinformation, digital literacy, and sociocultural factors is crucial in international conflict. This study investigates these connections and their significant impact on contemporary conflicts. It explores how historical events, cultural norms, and societal values shape public perception and responses to information distributed through various media channels. Emphasis is placed on the growing challenge of disinformation, where malicious actors manipulate information ecosystems to manipulate narratives and provoke conflict. Utilizing a qualitative approach, this study illustrates how Russia and Ukraine use media for propaganda, highlighting new risks and underscoring the evolving importance of digital literacy as a critical defense mechanism.